Apakah Janji Langit Baru dan Bumi Baru sudah Ditepati? Analisis Historis Yesaya 65:17-25 - Sihotang, Henriko (DUNAMIS: Jurnal Teologi dan Pendidikan Kristiani, 2025)
Abstract. The theologians’ views (especially those who come from the patristic view) regarding the concept of the New Heaven and New Earth (Isa. 65:17-25), come to the conclusion that the fulfillment of the promise is with the coming of a new heaven and a new earth that will replace the recent heaven and earth. Through the historical interpretation of the text, I try to show the historical meaning and purpose of the concept. I focus this research on the history of the text by considering the context of the people as recipients of the core message of the book of Isaiah and its subsequent influence. The context of the recipients or initial readers of the text is the basis for the analysis in this study. I argue that the prioritization of the reconstruction of the Temple after the Babylonian exile as a focal point as well as a sign of God's presence blessing and fulfilling His promises by realizing the vision of the promised New Heaven and New Earth. Which means that the promise of the New Heaven and New Earth has been fulfilled.Abstrak. Pandangan para teolog (terutama yang berangkat dari pandangan kaum patristik) terkait konsep Langit Baru dan Bumi Baru (Yes. 65:17-25), sampai pada kesimpulan penantian penggenapan janji tersebut dengan hadirnya langit baru dan bumi baru kelak yang menggantikan langit dan bumi yang lama. Melalui tafsir historis teks, saya berupaya memperlihatkan makna dan tujuan awal konsep tersebut. Saya memfokuskan penelitian ini atas sejarah teks dengan melihat konteks dari sudut keberadaan umat selaku penerima pesan inti kitab Yesaya tersebut dan pengaruh setelahnya. Konteks penerima atau pembaca awal teks tersebut menjadi dasar analisis pada kajian ini. Saya berargumen bahwa pengutamaan pembangunan kembali Bait Suci pascapembuangan Babel sebagai titik fokus sekaligus tanda kehadiran Tuhan memberkati dan memenuhi janji-janji-Nya dengan mewujudkan visi Langit Baru dan Bumi Baru yang dijanjikan itu. Yang artinya, bahwa janji Langit Baru dan Bumi Baru telah digenapi.